Combating Corruption in the Philippines : An Update - World Bank (Washington, DC, 2013)
The war against corruption in the Philippines has taken a fresh turn with the inauguration of President Gloria Macapagal-Arroyo on January 20, 2001, and the subsequent installation of the new government. Addressing corruption was one of the new administration's announced priorities, but a detailed anticorruption strategy and detailed action plan have yet to emerge. As this report notes, the deterioration of the governance environment in 2000 seems to have taken a heavy toll on investor confidence . The report also notes that several new initiatives were born during 2000-01 as the need for combating corruption was felt more widely and urgently. This need for concrete and visible actions to combat corruption still exists, maybe to a greater degree now than in the past. Chapter 1 discusses the 9-point approach to fighting corruption in the Philippines as proposed by the World Bank in November 1999 which comprises policy reforms and deregulation, reforming campaign finance, increasing public oversight, reforming the budget process, improving meritocracy in civil services, targeting selected agencies, enhancing sanctions, developing private sector partnerships, and supporting judicial reform. Chapter 2 discusses the widening government deficit begun in late 1999 and the events shaping this change. Chapter 3 highlights the areas where progress was made during this time and focuses on the emergence of new initiatives. Finally, Chapter 4 addresses the new Government's commitment.